THE TEACHING OF AL-KHOREZMI AND ITS CURRENT SIGNIFICANCE IN THE THIRD RENAISSANCE OF UZBEKISTAN - Tukhtaeva Nargiskhon Isamutdinovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article substantiates the scientific contribution to various sciences of Al-Khorezmi on the development of society and the influence of the thinker’s teachings on the First Renaissance in Central Asia in the X-XII centuries. The article argues that as a result of the heritage of the great scientist, you can acquire new important facts for the modern development of computer science and other exact and natural sciences. The concept of the scientist’s scientific ideas in the process of scientific development of modern Uzbekistan is analyzed.